Polyacetate and Polycarbonate RNA: Acylating Reagents and Properties - Habibian, Maryam (Org Lett, 2019)
Acylation of RNA at 2′-OH groups is widely applied in mapping RNA structure and recently for controlling RNA function. Reactions are described that install the smallest 2-carbon acyl groups on RNA—namely, 2′-O-acetyl and 2′-O-carbonate groups. Hybridization and thermal melting experiments are performed to assess the effects of the acyl groups on duplex formation. Both reagents can be employed at lower concentrations to map RNA secondary structure by reverse transcriptase primer extension (SHAPE) methods.